Translational Physiology of Anti-Müllerian Hormone: Clinical Applications in Female Fertility Preservation and Cancer Treatment - Rodgers, Rachael Jean; Abbott, Jason Anthony; Walters, Kirsty A.; Ledger, William Leigh (Frontiers in Endocrinology, 2021)
Background Whilst the ability of AMH to induce the regression of the Müllerian ducts in the male fetus is well appreciated, AMH has additional biological actions in relation to steroid biosynthesis and ovarian follicle dynamics. An understanding of the physiology of AMH illuminates the potential therapeutic utility of AMH to protect the ovarian reserve during chemotherapy and in the treatment of female malignancies. The translation of the biological actions of AMH into clinical applications is an emerging focus of research, with promising preliminary results. Objective and Rationale Studies indicate AMH restrains primordial follicle development, thus administration of AMH during chemotherapy may protect the ovarian reserve by preventing the mass activation of primordial follicles. As AMH induces regression of tissues expressing the AMH receptor (AMHRII), administration of AMH may inhibit growth of malignancies expressing AMHR II. This review evaluates the biological actions of AMH in females and appraises human clinical applications. Search Methods A comprehensive search of the Medline and EMBASE databases seeking articles related to the physiological functions and therapeutic applications of AMH was conducted in January 2020. The search was limited to studies published in English. Outcomes AMH regulates primordial follicle recruitment and moderates sex steroid production through the inhibition of transcription of enzymes in the steroid biosynthetic pathway, primarily aromatase and 17a-hydroxylase/17,20- lyase. Preliminary data indicates that administration of AMH to mice during chemotherapy conveys a degree of protection to the ovarian reserve. Administration of AMH at the time of ovarian tissue grafting has the potential to restrain uncontrolled primordial follicle growth during revascularization. Numerous studies demonstrate AMH induced regression of AMHR II expressing malignancies. As this action occurs via a different mechanism to traditional chemotherapeutic agents, AMH has capacity to inhibit proliferation of chemo-resistant ovarian cancer cells and cancer stem cells. Wider implications To date, AMH has not been administered to humans. Data identified in this review suggests administration of AMH would be safe and well tolerated. Administration of AMH during chemotherapy may provide a synchronistic benefit to women with an AMHR II expressing malignancy, protecting the ovarian reserve whilst the cancer is treated by dual mechanisms.